Temporal and spatial dynamics of thalamus-evoked activity in the anterior cingulate cortex - Chang, Wei-Chih; Lee, Chia-Ming; Shyu, Bai-Chuang (Neuroscience, 2012)
► Using multielectrode array recording to illustrate the spatial–temporal progression. ► The progress along a deep surface–deep trajectory loop across the cingulate cortex. ► Glutamatergic neurotransmitters were crucially involved. ► Opioid interneurons may play a modulatory role. In the present study, multielectrode array (MEA) recording was used to illustrate the spatial–temporal progression of anterior cingulate cortex (ACC) activity following stimulation of the thalamus in a thalamocingulate pathway-preserved slice. The MEA was placed under the slice that contained the ACC, and 60 channels of extracellular local field potentials evoked by bipolar electrical stimulation within the thalamus were analyzed. Several distinct thalamic-evoked responses were identified. The early negative component (N1; amplitude, −35.7±5.9μV) emerged in layer VI near the cingulum 8.4±0.5ms after stimulation. N1 progressed upward to layers V and II/III in a lateral-to-medial direction. Subsequently, a positive component (P; amplitude, 27.0±3.2μV) appeared 12.0±0.6ms after stimulation in layer VI. At 26.8±1.1ms, a second negative component (N2; amplitude, −20.9±2.7μV) became apparent in layers II/III and V, followed by a more ventrolateral component (N3; amplitude, −18.9±2.9μV) at 42.8±2.6ms. These two late components spread downward to layer VI in a medial-to-lateral direction. The trajectory paths of the evoked components were consistently represented with varied medial thalamic stimulation intensities and sites. Both AMPA/kainate and N-methyl-D-aspartate-type glutamate receptors involved in monosynaptic and polysynaptic transmission participated in this thalamocortical pathway. Morphine mainly diminished the two negative synaptic components, and this suppressive effect was reversed by naloxone. The present study confirmed that functional thalamocingulate activity was preserved in the brain-slice preparation. The thalamus-evoked responses were activated and progressed along a deep surface-deep trajectory loop across the ACC layers. Glutamatergic neurotransmitters were crucially involved in information processing. Opioid interneurons may play a modulatory role in regulating the signal flows in the cingulate cortex.